Conjugated linoleic acid reduces body weight gain in ovariectomized female C57BL/6J mice - Kanaya, Noriko (2010)
Estrogen is an important protective factor against obesity in females. Therefore, postmenopausal women have a higher rate of obesity than premenopausal women, which is associated with age-related loss of ovary function. It has been reported that a diet containing conjugated linoleic acid (CLA) reduced body weight and body fat mass in the animal model as well as in human trials. We hypothesized that ingestion of CLA would reduce body weight gain in ovariectomized (OVX) female C57BL/6J mice which is a model for postmenopaual women. We further hypothesized that body weight reduction may improve obesity-related complication. To test this hypothesis, the OVX mice fed with a high fat diet containing CLA for 3 months. Mice had significantly reduced body weight gain compared to OVX mice fed with a high fat diet without CLA. While CLA was effective in slowing down of body weight gain of both Sham and OVX mice, analysis of adipocyte size and number suggested different mechanisms for loss of fat tissue in these two groups of mice. CLA treatment did not increase liver weight and accumulation of fat in the livers of OVX mice. Furthermore, CLA intake did not change insulin resistance. Our results indicate that CLA is functional as an anti-obesity supplement in the mouse model for postmenopausal women, and the anti-obesity effect of CLA is not estrogen-related.